Lack of GAGA protein in Trl mutants causes massive cell death in Drosophila spermatogenesis and oogenesis - N. V. Dorogova; A. E. Zubkova; E. V. Fedorova; E. U. Bolobolova; E. M. Baricheva (Вавиловский журнал генетики и селекции)
Drosophila protein GAGA (GAF) is a factor of epigenetic transcription regulation of a large group of genes with a wide variety of cellular functions. GAF is encoded by the Trithorax-like (Trl) gene, which is important for the formation of various organs and tissues at all stages of ontogenesis. In our previous works, we showed that this protein is necessary for the development of the reproductive system, both in males and females of Drosophila. Decreased expression of the Trl gene led to multiple disorders of spermatogenesis and oogenesis. One of the significant disorders was associated with massive degradation and loss of cells in the germline. In this work, we carried out a more detailed cytological study to determine what type of germ cell death is characteristic of Trl mutants, and whether there are disturbances or changes in this process compared to the norm. The results obtained showed that the lack of GAF protein causes massive germ cell death in both females and males of Drosophila, but this death manifests itself in different ways, depending on the sex. In Trl females, this process does not differ phenotypically from the norm. In the dying egg chambers, signs of apoptosis and autophagy were revealed, as well as morphological features that are characteristic of the wild type. In males, Trl mutations induce mass germ cell death through autophagy, which is not typical of Drosophila spermatogenesis, and has not been previously described, neither in the norm nor in other genes’ mutations. Thus, GAF lack in Trl mutants leads to increased germ cell death through apoptosis and autophagy. Ectopic cell death and germ line atrophy are probably associated with impaired expression of the GAGA factor target genes, among which there are genes that regulate both apoptosis and autophagy.